Voltammetry of Layered Black Phosphorus: Electrochemistry of Multilayer Phosphorene. Issue 3 (3rd December 2014) - Wang, Lu; Sofer, Zdenek; Pumera, Martin
Abstract Layered black phosphorus crystals were prepared by the chemical vapor transport method. It is characterized by scanning electron microscopy, energy‐dispersive X‐ray spectroscopy, X‐ray photoelectron spectroscopy and X‐ray diffraction. Black phosphorus exhibits inherent electrochemistry in the sense that it is oxidizable ∼560 mV (vs Ag/AgCl). This study is a first step in the utilization of black phosphorus, in modern days named as stacked phosphorene, in electrochemical applications.